Peru : Second Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper focuses on Peru's Second Review Under the Stand-By Arrangement (SBA). Progress was made on structural reforms, but key reforms remain to be implemented, including the completion of tax reform and implementation of a fiscally neutral decentralization. Both are crucial to fiscal sustainability over the medium term but face considerable risks in the current political environment. The 2003 program aims at maintaining prudent macroeconomic policies, including moderate fiscal adjustment, and pressing ahead with structural reforms. Moderate fiscal adjustment is also needed to give credibility to the authorities' medium-term deficit target.